Optimal design of electric bicycle : bicycle frame design - Mohamad Firdaus, Omar (2013)
This projek discuss the suitable design for electric bicycle and also the material for the bicycle frame. With the addition of motor and battery pack on the electric bicycle, the body frame have extra load to overcome other than rider weight. Therefore an analysis by using Finite Element Analysis method will be done to determine the most efficient design and the suitable material for the electric bicycle’s frame.